Pain interventions in adults with intellectual disability: A scoping review and pharmacological considerations. (9th March 2020) - Lonchampt, Sophie; Gerber, Fabienne; Aubry, Jean‐Michel; Desmeules, Jules; Kosel, Markus; Besson, Marie
Abstract: Background and Objective: Having to deal on a daily routine with prescriptions in adults with intellectual disability (ID), we systematically reviewed the literature on the specificities of pain interventions in that population, focusing on medication and trying to gather practical information on appropriate pain treatments. Given the scarcity of the literature on the topic, we also discussed the pharmacological considerations to be taken into account when prescribing analgesic drugs in that vulnerable population. Databases and Data Treatment: Articles on pain and ID were searched in the Medline and Google scholar electronic databases using the key words "Intellectual Disability, " "Developmental Disability" and specific keywords for pharmacological and non‐pharmacological pain interventions. Preset outcomes about pharmacological treatment specificity, efficacy and safety were then collected. Results: One hundred and fifty‐two articles were found and 16 were retained based on our inclusion and exclusion criteria. Of the 16 articles, five were topical reviews. Among the 11 remaining articles, five discussed pharmacological interventions, four considered non‐pharmacological interventions and two discussed both. As anticipated, the literature matching our specific outcomes about the pharmacological treatment of pain was scarce and for the most part not designed to answer the questions of specificity, efficacy and safety of pain treatment in adults with ID. Conclusion: The specificity of analgesic treatments in adults with ID is a totally unexplored domain. In the absence of clinical guidelines, pharmacological facts—such as inter‐individual variability in drug response, pharmacokinetic and pharmacodynamic interactions, frequent co‐morbidities and ease of administration—must be systematically integrated, when prescribing in the population of adults with ID. Significance: This review synthesizes the state of research on pain interventions in adults with ID and is one of the rare articles addressing the specificities of analgesic prescriptions in this population.